Land Use Planning in Pastoral Areas - Flintan, Fiona E. (International Livestock Research Institute, 2022)
Presentation on Land use planning in pastoral areas by Fiona Flintan in October 2022 at the IGAD High Level Regional Conference on Land and Conflict.